Sudan : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that Sudan's economic performance in 2012 was unfavorable despite the introduction in June 2012 of a package of reforms. Non-oil real GDP growth slowed to 4.6 percent, inflation rose to 44.4 percent by the end of the year, and the gap between the official and curb market exchange rates remained at about 20 percent by end-December. The outlook for 2013 and the medium term are unfavorable. Non-oil real GDP growth is projected to slow further to 2.3 percent in 2013, and to remain below potential at about 3 percent over the medium term.